2019
DOI: 10.1093/mnras/stz2147
|View full text |Cite
|
Sign up to set email alerts
|

A common origin for the circumnuclear disc and the nearby molecular clouds in the Galactic Centre

Abstract: The origin of the molecular clouds orbiting SgrA* is one of the most debated questions about our Galactic Centre. Here, we present the hydrodynamic simulation of a molecular cloud infalling towards SgrA*, performed with the adaptive-mesh-refinement code RAMSES. Through such simulation, we propose that the circumnuclear disc and the +20 km/s cloud originated from the same tidal disruption episode, occurred less than 1 Myr ago. We also show that recent star formation is to be expected in the +20 km/s cloud, as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…They concluded that supernova feedback associated with the intense star formation activity in the CMZ can generate an inflow rate of ∼ 0.03 M yr −1 (< 5% of the inflow rate from large-scales; §4.1.1), by stochastically launching parcels of gas towards the centre and/or by randomly changing their angular momentum. At this rate the CND would only take ∼ 3 Myr to build up, consistent with the view inferred from observations that the CND is a transient structure on this timescale (Requena-Torres et al 2012;Mapelli and Trani 2016;Ballone et al 2019;Dinh et al 2021, §2.1.4).…”
Section: From the Cmz To The Nucleussupporting
confidence: 85%
See 1 more Smart Citation
“…They concluded that supernova feedback associated with the intense star formation activity in the CMZ can generate an inflow rate of ∼ 0.03 M yr −1 (< 5% of the inflow rate from large-scales; §4.1.1), by stochastically launching parcels of gas towards the centre and/or by randomly changing their angular momentum. At this rate the CND would only take ∼ 3 Myr to build up, consistent with the view inferred from observations that the CND is a transient structure on this timescale (Requena-Torres et al 2012;Mapelli and Trani 2016;Ballone et al 2019;Dinh et al 2021, §2.1.4).…”
Section: From the Cmz To The Nucleussupporting
confidence: 85%
“…The exact mechanism by which gas is transported from the CMZ to the inner 10-20 parsecs is an open question ( §4.1). However, there is some evidence that the CND is built up from the tidal disruption of molecular clouds located within the inner ∼ 10-20 pc (Ho et al 1991;Coil and Ho 2000;McGary et al 2001;Martín et al 2012;Mapelli and Trani 2016;Hsieh et al 2017Hsieh et al , 2019Tsuboi et al 2018;Ballone et al 2019). Several filamentary molecular gas structures, or "streamers", have been detected surrounding the CND.…”
Section: The Circumnuclear Discmentioning
confidence: 99%
“…(ii) They appear to be morphologically and kinematically connected to gaseous structures in the immediate vicinity SgrA * , such as the CND (Okumura et al 1991;Coil & Ho 2000;Liu et al 2012;Hsieh et al 2017;Takekawa, Oka & Tanaka 2017;Tsuboi et al 2018;Ballone, Mapelli & Trani 2019).…”
Section: The 20 and 50 Km S −1 Cloudsmentioning
confidence: 99%
“…Based on the observation that the CND appears to be disequilibrated because of the presence of internal transient structures, many publications model the formation of the CND as a recent event that resulted from the infall of a dense cloud toward the central black hole (Sanders 1998;Bradford et al 2005;Bonnell & Rice 2008;Wardle & Yusef-Zadeh 2008;Hobbs & Nayakshin 2009;Alig et al 2011;Oka et al 2011;Mapelli et al 2012;Mapelli & Trani 2016;Trani et al 2018;Goicoechea et al 2018;Ballone et al 2019). The idea rests on the assumption that a relatively massive cloud with a very small total angular momentum can somehow be produced near the black hole, or can be produced further away, but be unimpeded in its accelerating trajectory toward the black hole.…”
Section: Origin and Longevity Of The Cndmentioning
confidence: 99%
“…A popular model to account for the transient structures within the CND is that a passing cloud was gravitationally captured by the black hole. This "infalling cloud" was then tidally disrupted into what is now the CND (Sanders 1998;Bradford et al 2005;Bonnell & Rice 2008;Wardle & Yusef-Zadeh 2008;Hobbs & Nayakshin 2009;Alig et al 2011;Oka et al 2011;Mapelli et al 2012;Mapelli & Trani 2016;Trani et al 2018;Goicoechea et al 2018;Ballone et al 2019).…”
Section: Introductionmentioning
confidence: 99%